2017
DOI: 10.21037/tgh.2016.12.01
|View full text |Cite
|
Sign up to set email alerts
|

Distant nodal metastasis: is it always an unresectable disease?

Abstract: This article aims at analyzing the published literature concerning the treatment of patients with gastric cancer and distant nodal metastases, actually considered metastatic disease. A systematic search was undertaken using Medline, Embase, Cochrane and Web-of-Science libraries. No specific restriction on year of publication was used; preference was given to English papers. Both clinical series and literature reviews were selected. Only 11 papers address the issue of surgery for nodal basins outside the D2 dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The final risk function was H(t) = [h 0 (t)]e (0.922 ×6+1.99 ×8+1.657 ×9) , suggesting that these factors all affect the outcome of NSCLC patients and their risk coefficients were reached at 0.922 and 1.99 respectively. As we all know, once lymph node metastasis and distant metastasis take place, the survival time of patient with malignant tumors will be remarkably shortened, and will also lead to a great adverse to the treatment 27 . Through our results, it is suggested that HSP27 can be used as a new tumor marker to evaluate the prognosis of NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…The final risk function was H(t) = [h 0 (t)]e (0.922 ×6+1.99 ×8+1.657 ×9) , suggesting that these factors all affect the outcome of NSCLC patients and their risk coefficients were reached at 0.922 and 1.99 respectively. As we all know, once lymph node metastasis and distant metastasis take place, the survival time of patient with malignant tumors will be remarkably shortened, and will also lead to a great adverse to the treatment 27 . Through our results, it is suggested that HSP27 can be used as a new tumor marker to evaluate the prognosis of NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…However, acute pancreatitis is a little-known complication of hydatid disease. The primary pancreatic location of hydatid cyst actually represents less than 1% of all cases reported in the literature [ 5 , 6 ]. It is responsible for a few cases of acute pancreatitis by cyst compression or migrated vesicle daughters’ obstruction of the main pancreatic duct [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…GC, being the fifth most commonly occurring cancer, is prevalent in the eastern and central parts of Asia and is the third most common cancer as per the mortality rate [ 3 , 4 ]. Mizoram, Northeastern tribal state of India has the highest incidence rate of gastric cancer in India [ 5 ] and globally occupies the fifth position for GC [ 6 ].…”
Section: Introductionmentioning
confidence: 99%